Survival analysis of Thai micro and small enterprises during the COVID-19 pandemic - Leurcharusmee, Supanika; Maneejuk, Paravee; Yamaka, Woraphon; Thaiprasert, Nalitra; Tuntichiranon, Nathapong (Journal of Business Economics and Management, 2022)
Micro and small enterprises (MSEs) are important to the local economy and are the most crucial source of employment in Thailand. Using the three-round survey data, we assess the impact of COVID-19 on the survival probability of MSEs in the tourism and manufacturing sectors. Enterprise characteristics such as owner characteristics, employment and business strategies are examined as potential factors to mitigate or stimulate business failures. The Cox proportional hazards model and Kaplan–Meier estimator are employed. Our findings reveal that the survival probability paths from the three rounds of survey show a gradual decrease of survival probability from the first week of interview and approximately 50% of MSEs could not survive longer than 52 weeks during the COVID-19 pandemic. We also find that the survival of MSEs mainly depends on location, number of employees, and business model adjustment, namely operation with social distancing and online marketing. Particularly, retaining employees and not reducing the working hours are one of the key factors increasing the survivability of MSEs. However, the longer length of the crisis reduces the contribution of these key factors. The longer the period of the COVID-19 pandemic, the lower the chance of MSEs survivability.